Zero-valent species of group 13–15 elements - Ota, Kei (2022)
This perspective describes the development of zero-valent species En(0) of group 13–15 elements. Computational studies providing reinterpretation of bonding involved in well-known molecules, such as carbodiphosphorane, have opened up the area. Employment of Lewis bases to form donor-acceptor interactions with the elemental fragments in the zero oxidation state is the key to stabilizing such species. Because of the diversity of Lewis bases available, En(0) derivatives with a variety of bonding and structural motifs are isolable. The monoatomic E1(0) species of group 13 and 15 elements, middle-size En(0) clusters (n = 4–6) of group 13 and 14 elements, and the heavier group 13 cousins have been much less explored. The end of the article outlines one of the potential future directions of zero-valent main-group chemistry, which is an exploration of the allotrope chemistry relevant to materials science.